Impact of lower calyceal anatomy and stone size on stone clearance after extracorporeal shock wave lithotripsy (eswl) in adults - Chiang, Yoong Fei (2012)
This study was conducted to evaluate the impact of radiological anatomy of the lower calyx and stone size on lower pole stone clearance after extracorporeal shock wave lithotripsy (ESWL) in adults. We retrospectively evaluated 20 patients with age older than 18, who had ESWL at USM Hospital within 25 months (September 2009 till September 2011) for radio-opaque lower pole calculi with the largest diameter up to 20mm. Stone size and lower pole anatomy, as defined by the infundibulopelvic angle, infundibular length and width were assessed in pre-ESWL intravenous urogram (IVU). All patients were treated with ESWL and outcome of the stone clearance were reviewed in KUB radiograph performed 1-4 months after the last ESWL. Only 10 patients (50%) of the study were stone-free after ESWL. Mean stone size and infundibular length were 14.36mm ± 3.98mm and 27.79mm ± 6.52mm respectively. Median infundibulopevic angle and infundibular width were 33.0° (IqR = 19.75°) and 4.90mm (IqR = 6.45mm) respectively. No statistically significant difference found in all IVU parameter means or medians between stone-free group and residual stone group. There was also no association of any IVU parameters with stone-free status. Stone size and lower calyceal anatomy have no significant impact on stone clearance after ESWL. However, further examination of the IVU parameters and further explore for other contributing factors are still warranted.